Ocular Aberrations and Corneal Shape in Adults with and without Astigmatism - Tsz-Wing Leung; Andrew Lam; Chea‐su Kee (2015)
To characterize and compare the corneal shapes and monochromatic aberrations in Chinese myopic adults with and without astigmatism.Forty-six Hong Kong Chinese aged 50 to 70 years with compound against-the-rule myopic astigmatism (n = 18) or simple myopia (n = 28) were recruited. Corneal shapes were measured by a Scheimpflug-based corneal topographer: the semimeridian corneal shape factors at the nasal, temporal, inferior, and superior corneal quadrants measured from the corneal apex to 3 mm midperiphery were analyzed. The ocular aberrations were measured by the COAS (Complete Ophthalmic Analysis System) Shack-Hartmann wavefront aberrometer; the corneal aberrations were computed using the corneal topographic map data measured by the Medmont E300 corneal topographer; and the internal aberrations were calculated from the ocular and corneal aberrations.Compared with simple myopia, myopic astigmatism had more oblate nasal and temporal corneal shapes and showed significantly more negative Y trefoil and more positive vertical coma. The asymmetry in corneal shape along the vertical principal meridian (inferior - superior) was significantly associated with the Y trefoil and vertical coma of the cornea, suggesting that this regional asymmetry in corneal shape may contribute to the ocular aberrations.The significant relationships found between astigmatism, corneal shapes, and monochromatic aberrations underscore the importance of taking corneal shape into account when correcting the optical defects in myopic Chinese adults with astigmatism.